The development of a fully integrated, outcomes based, whole system framework of public sector commissioning for the health and wellbeing of the population. - McMahon, Jamie (2019)
Integration of public services is a key policy objective for every government and policy maker, ever increasingly so. However, the history of successful public sector integration is one of failed ambition. At a time when public services face increased demand and significant budget pressures the desire for integration of public services has grown, especially health and social care integration.